P2P Loan Management System Using Blockchain in 6G Network System - Gayke, P.S; Gajanan Badak, Pawan; Namdev Pund, Dipak; Dattatray Jawale, Rushikesh; Bhausaheb Kotkar, Mayur; Gaware, Sarthak Shantilal (International Journal of Computer Sciences and Engineering, 2024)
Decentralized, secure platform that aids in managing loan operations is the loan management system that uses blockchain technology. Through the use of blockchain`s distributed ledger technology, security, immutability, and transparency are guaranteed. The loan lifecycle may be managed with this system in an open and effective manner, from the point of loan application to loan payback. Every stage of the loan application process is documented on the blockchain, resulting in an irreversible and permanent record of all transactions. The loan management system automates a number of loan-related tasks, including loan application, credit evaluation, approval, and disbursal, by using smart contracts. This guarantees more accuracy and transparency, gets rid of the need for middlemen, and shortens processing times